Mechanistic study of Jiawei Zicao Plaster in atopic dermatitis via IL-17 signaling pathway and skin microbiome modulation - Wang, Andong; Chen, Tingting; Zhang, Hongtao; Yang, Yuru; Cheng, Xiaotian; Chen, Di; Ling, Bai (Frontiers in Microbiology, 2025)
BackgroundAtopic dermatitis (AD) is a prevalent and difficult-to-cure chronic inflammatory skin condition. The mechanism of Jiawei Zicao Plaster (JZP), a clinically used Traditional Chinese Medicine (TCM) for AD, remains incompletely understood.MethodsFollowing successful model induction, JZP was topically applied to the dorsal skin of mice. Therapeutic efficacy was evaluated through histopathological examination of skin sections and quantification of inflammatory biomarkers using ELISA. To investigate the underlying mechanisms, we performed qRT-PCR to analyze gene expression in related signal pathway, along with 16S rRNA sequencing to characterize skin microbiota composition.ResultsNetwork pharmacological analysis revealed that JZP may exert therapeutic effects by targeting antibacterial and anti-inflammatory pathways. Subsequent in vivo experiments demonstrated that JZP effectively ameliorates biochemical markers of AD by activating the IL-17 pathway. Analysis of skin microbiota indicated that JZP treatment led to an increase in Chryseobacterium abundance and a decrease in Staphylococcus abundance.ConclusionThis study seeks to validate the efficacy of JPZ as a treatment for AD. Initial findings suggest that JPZ attains its therapeutic efficacy through the synergistic actions of IL-17 and antibacterial properties, providing a theoretical basis for the future development and application of this traditional Chinese medicine formula.